2014
DOI: 10.2466/21.09.pr0.114k23w6
|View full text |Cite
|
Sign up to set email alerts
|

Personality Variables as Predictors of Facebook Usage

Abstract: This study investigates the role of personality factors as predictors of Facebook usage. Data concerning Facebook usage and personality factors from 654 Facebook users were gathered using a web survey. Using path analysis, the results showed Openness was a predictor of Facebook early adoption, Conscientiousness with sparing use, Extraversion with long sessions and abundant friendships, and Neuroticism with high frequency of sessions. The possible role of Agreeableness in predicting low session frequency and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 25 publications
9
45
1
Order By: Relevance
“…The positive correlations we found between Facebook intensity, Reward Interest, Reward Reactivity and Impulsivity were in line with our hypotheses and concur with findings from previous research on the FFM personality traits and frequency of Facebook use for individuals high in Openness to Experience, Extraversion, and low in Conscientiousness (Andreassen, Torsheim, Brunborg, & Pallesen, 2012;Caci et al, 2014;Correa et al, 2010;Ryan & Xenos, 2011). Research has found that people on both sides of the Extraversion scale demonstrate elevated SNS use; as those high in Extraversion use SNS for social enhancement, while those low in Extraversion use SNS for social compensation (Kuss & Griffiths, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The positive correlations we found between Facebook intensity, Reward Interest, Reward Reactivity and Impulsivity were in line with our hypotheses and concur with findings from previous research on the FFM personality traits and frequency of Facebook use for individuals high in Openness to Experience, Extraversion, and low in Conscientiousness (Andreassen, Torsheim, Brunborg, & Pallesen, 2012;Caci et al, 2014;Correa et al, 2010;Ryan & Xenos, 2011). Research has found that people on both sides of the Extraversion scale demonstrate elevated SNS use; as those high in Extraversion use SNS for social enhancement, while those low in Extraversion use SNS for social compensation (Kuss & Griffiths, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is plausible that individuals low on Conscientiousness would display impulsive traits. Previous research on Facebook use has found that people who are high on Conscientiousness used Facebook less than those who are low on Conscientiousness (Caci et al, 2014;Ryan & Xenos, 2011). We therefore surmise that respondents who have high Impulsivity will use Facebook more intensively than those with low Impulsivity.…”
Section: Social Networking Sites and Personalitymentioning
confidence: 64%
See 2 more Smart Citations
“…Moreover, Ryan and Xenos (2011) not only confirmed this finding but also came to the conclusion that neuroticism is positively correlated with the time spent on Facebook. Similarly, another study by Caci et al (2014) found neuroticism to be predictive for the frequency and duration of everyday Facebook use.…”
Section: Personality Traits and Facebook Usementioning
confidence: 81%